ABCG2 and CD200 define patients at high risk of relapse in ELN favorable subgroup of AML. (20th July 2017) - Tiribelli, Mario; Geromin, Antonella; Cavallin, Margherita; Di Giusto, Sara; Simeone, Erica; Fanin, Renato; Damiani, Daniela
Abstract: Objective: Overexpression of ABCG2 and CD200 has been independently associated with poor outcome in acute myeloid leukemia (AML). However, no data are available on the role of these two factors in patients with core‐binding factor (CBF)‐positive or FLT3‐negative/NPM1‐mutated cytogenetically normal (CN) AML. Methods: We analyzed 65 adult AML patients with CBF+ (n=16) or FLT3−/NPM1+ CN (n=49), evaluating clinical and biological factors associated with complete remission attainment, leukemia‐free survival (LFS) and overall survival (OS). Results: ABCG2 was expressed in 36 (55%) cases, and CD200 was positive in 33 (51%) cases, six at high levels. Both ABCG2 and CD200 positivity have a negative impact on relapse risk: 3‐year LFS was 51% vs 82% in ABCG2+ cases (RR 3.3), 49% vs 82% in CD200+ patients (RR=4.4), and 25% in CD200− high cases (RR=17.1). ABCG2 and CD200 affected also OS with 3‐year OS of 39% in ABCG2+ (compared to 71% in ABCG2−; RR=2.6) and CD200+ (compared to 68% in CD200−; RR=2.5) patients. Conclusions: Our data confirm a negative impact of ABCG2 and CD200 overexpression also in AML patients considered at favorable risk according to ELN cytogenetic/molecular classification.